Associated factors of depression severity among school-going adolescents in Malaysia from national school based health survey 2012 - Sahril, Norhafizah (2018)
Introduction: Depression is the single largest contributor to the global burden of disease. Depression was found as a common disorders among children lower than 18 years old. Objective: The objectives of this study are to estimate the prevalence of depression according to severity and to determine the factor associated with severity of depression among school-going adolescents in Malaysia. Method: Secondary data analysis from Malaysian National School Based Health Survey 2012 was conducted. From Mental Health Survey database, a total of 24,276 respondent have responded to depression module in DASS-21. While, the total number of respondent that responded to all module in Global School based Health Survey (GSHS) was 25,410. Finally after merged the database and taking consideration of inclusion and exclusion criteria of the study, a total of 21,764 school-going adolescents aged 12 to 18 years old were eligible in this study. No additional or further sampling was done on the obtained data which was taken with GSHS original sampling design scheme which engaged stratification and clustering. Socio demographics characteristics, substance use, health behaviour, home and environment and comorbidities factor were extracted from the database. Looking for depression severity, it was categorised as normal, mild, moderateand severe. Complex Sample ordinal logistic regression was used for analysis to quantify the odds ratio and 95 % confidence interval. Results: A total of 21,764 adolescents were included in the study with the mean (SD) age of 14.19 (1.47). The overall prevalence of depression symptoms was 33.2% (95% CI: 32.0, 34.4). The prevalence of mild, moderate and severe depression were 16.6% (95% CI: 16.08, 17.27), 12.8% (95% CI: 12.04, 13.53) and 3.8% (95% CI: 3.38, 4.22) respectively. In multivariable analysis, the higher odds of having more severe depression was observed among females (OR=1.32, 95% CI: 1.21, 1.43), Indian ethnicity (OR=1.73, 95% CI: 1.42, 2.10), those who smoke (OR=1.30, 95% CI: 1.15, 1.46), drink alcohol (OR=1.30, 95% CI: 1.14, 1.48), take drug (OR=1.81, 95% CI: 1.24, 2.65), involved in truancy (OR=1.31, 95% CI: 1.20, 1.43), those who have been bullied (OR=1.84, 95% CI: 1.68, 2.01), those who had suicidal ideation (OR=3.02, 95% CI: 2.56, 3.55), lack of parental bonding (OR=1.33, 95% CI: 1.22, 1.45), and lack of parental connectedness (OR=1.29, 95% CI: 1.19, 1.40). Conclusion: One third of adolescents were reported have symptoms of depression. The prevalence of depression by severity were higher in mild followed by moderate and severe depression. Complex Sample ordinal logistic regression analysis revealed that female, Indian ethnic, substance use risk factor, health behavior risk factor and home and school environment risk factor were likely to be associated in having more severe depression.